The Effect of Dragon Tail Leaf Extract (Epipremnum pinnatum (L.) Engl) on Blood Glucose in Rats with Diabetes Mellitus - Feby Larasati; Rauza Sukma Rita; Gestina Aliska (ARMADA : Jurnal Penelitian Multidisiplin, 2026)
Diabetes mellitus is a metabolic disorder characterized by elevated blood glucose levels exceeding normal limits (hyperglycemia) due to impaired insulin secretion by the pancreas. One alternative treatment being developed is the use of medicinal plants with antidiabetic activity. Dragon's tail leaf (Epipremnum pinnatum (L.) Engl.) is known to contain secondary metabolites such as flavonoids, alkaloids, saponins, and phenolics that have the potential to lower blood glucose levels. The purpose of this study was to determine the effect of dragon's tail leaf extract on blood glucose levels in rats with diabetes mellitus. This experimental study used a pre-test-post-test control group design. Thirty-six rats were divided into six groups: K(-) as normal controls, K(+) as diabetic controls induced by alloxan at 100 mg/kgBW, Kmet as a comparison group induced by metformin at 250 mg/kgBW, and treatment groups P1, P2, and P3, which were administered dragon's tail leaf extract at varying doses of 125, 250, and 375 mg/kgBW. Diabetes induction was performed using alloxan to induce hyperglycemia. Blood glucose levels were measured using the POCT method. The results showed that administration of dragon's tail leaf extract (Epipremnum pinnatum (L.) Engl.) reduced blood glucose levels in diabetic rats (p=0.001). Thus, dragon's tail leaf extract has potential as a natural antihyperglycemic agent in the management of diabetes mellitus.